Peran Masjid dalam Pengembangan Sosial dan Ekonomi Masyarakat - Mardi, Moh (Prodi Ekonomi Syariah STAI Syaichona Moh. Cholil Bangkalan, 2024)
Mosques hold a vital role in the socio-economic development of Muslim communities, serving not only as places of worship but also as hubs for education, social services, and economic empowerment. This study explores the multifaceted functions of mosques in Indonesia, focusing on their contributions to social welfare and local economic growth. Using a qualitative case study approach, data were collected through interviews, participatory observations, and document analysis at mosques actively engaged in social and economic initiatives. Findings reveal that mosques contribute significantly to community development through educational programs, healthcare services, and humanitarian aid while also supporting economic activities via microenterprise training, cooperative management, and efficient utilization of zakat funds. Despite these achievements, challenges such as limited resources, management skills, and public engagement were identified as barriers to optimizing mosque programs. The study recommends enhancing mosque management capabilities, fostering partnerships with governmental and private organizations, and adopting transparent financial practices to maximize community impact. These insights underscore the potential of mosques to serve as comprehensive centres for societal advancement.